1998
DOI: 10.1677/joe.0.1590257
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age-dependent changes in the levels of mRNAs encoding cortisol biosynthetic enzymes and IGF-II in the adrenal gland of fetal sheep during prolonged hypoxemia

Abstract: Hypoxemia represents a major stress for the fetus, and is associated with alterations and adaptations in cardiovascular, metabolic and endocrine responses, which in turn may affect tissue growth and differentiation. To determine the effects of hypoxemia on fetal adrenal activity and growth, we subjected sheep fetuses at days 126-130 and 134-136 (term 145 days) to reduced PaO 2 by reducing the maternal fraction of oxygen for 48 h (mean reduction of 6·8 mmHg), without change in arterial pH or PaCO 2 . This stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…In contrast, 24 h of restricted uterine blood flow (RUBF) in ovine fetuses aged between 115 and 120 days of gestation resulted in a significant decline in liver IGF-I mRNA and only a tendency for IGF-II mRNA to decrease (McLellan et al 1992). We observed no changes in tissue IGF-I or -II mRNA levels in the near-term group in response to UCO, although previous work in late-gestation (126-130 and 134-136 days of gestation) ovine fetuses has shown that 48 h of acute isocapnic hypoxia reduced IGF-II mRNA expression in the adrenal gland (Braems et al 1998). Our results suggest a greater susceptibility of IGF-II gene expression to UCO in younger fetuses, in which IGF-II mRNA levels are higher (Delhanty & Han 1993).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In contrast, 24 h of restricted uterine blood flow (RUBF) in ovine fetuses aged between 115 and 120 days of gestation resulted in a significant decline in liver IGF-I mRNA and only a tendency for IGF-II mRNA to decrease (McLellan et al 1992). We observed no changes in tissue IGF-I or -II mRNA levels in the near-term group in response to UCO, although previous work in late-gestation (126-130 and 134-136 days of gestation) ovine fetuses has shown that 48 h of acute isocapnic hypoxia reduced IGF-II mRNA expression in the adrenal gland (Braems et al 1998). Our results suggest a greater susceptibility of IGF-II gene expression to UCO in younger fetuses, in which IGF-II mRNA levels are higher (Delhanty & Han 1993).…”
Section: Discussioncontrasting
confidence: 75%
“…These changes are associated with a reduction in the rate of DNA synthesis in specific organs and tissues (Hooper et al 1991, Asano et al 1997. A reduction in fetal growth, with associated changes in IGFs and IGFBPs, is likely to constitute tissue-specifc energy expenditure adaptations in the face of an altered substrate and/or oxygen supply and could be mediated, in part, by endocrine changes involving catecholamines (Hooper et al 1994) or cortisol (Braems et al 1998), for example.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Braems et al (6) showed that, in the older sheep fetuses, hypoxemia resulted in significantly increased levels of mRNAs encoding P450scc, P450C21, and 3␤-HSD (6). These results are similar to ours.…”
Section: Discussionsupporting
confidence: 85%
“…Sustained hypoxemia activates adrenal steroidogenesis in the older fetal sheep. The resultant increase in cortisol synthesis is associated with decreased expression of adrenal IGF-II mRNA (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the increase in cortisol contributes to regulation of ACTH-R mRNA expression. Alternatively, increased ACTH-R could enhance adrenal responsiveness and cortisol output, as mRNA levels encoding key steroidogenic enzymes were also increased in these fetuses (Braems et al 1998). Thus, with hypoxaemia, a feed-forward loop may be established, with increased cortisol synthesis driving enhanced adrenal responsiveness (Lye & Challis 1984), potentially resulting in preterm birth.…”
Section: Discussionmentioning
confidence: 99%